2010
DOI: 10.3109/00207451003597193
|View full text |Cite
|
Sign up to set email alerts
|

Kimmerle's Anomaly as a Possible Causative Factor of Chronic Tension-Type Headaches and Neurosensory Hearing Loss: Case Report and Literature Review

Abstract: Kimmerle's anomaly also known as ponticulus posticus is a common anatomical variation of the atlas, the first cervical vertebra. It is the product of the complete or incomplete ossification of the posterior atlanto-occipital membrane over the vertebral artery groove resulting in the formation of a foramen (arcuate foramen) containing the vertebral artery and the posterior branch of the C-1 spinal nerve. This variation has been associated with vertebro-basilar insufficiency symptoms, various types of headaches,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 6 publications
0
29
0
2
Order By: Relevance
“…The audiometric investigation concluded the hearing loss to be of the neurosensory type, whereas, the imaging examinations revealed the existence of a partial osseous bridge, that is an incomplete arcuate foramen on the upper surface of atlas. Both the clinical and the radiological findings of this case were indicative of a possible connection between Kimmerle's anomaly and the manifestation of chronic tension-type headaches and neurosensory-type hearing loss [12]. However, in contradiction to above mentioned study in which they found symptoms only in patients with partial or incomplete forms of PP, in our study, we found that patients with both the forms of ponticulus posticus had symptoms of tension type headache and migraine in the age group of 16-45 years.…”
Section: Resultsmentioning
confidence: 91%
“…The audiometric investigation concluded the hearing loss to be of the neurosensory type, whereas, the imaging examinations revealed the existence of a partial osseous bridge, that is an incomplete arcuate foramen on the upper surface of atlas. Both the clinical and the radiological findings of this case were indicative of a possible connection between Kimmerle's anomaly and the manifestation of chronic tension-type headaches and neurosensory-type hearing loss [12]. However, in contradiction to above mentioned study in which they found symptoms only in patients with partial or incomplete forms of PP, in our study, we found that patients with both the forms of ponticulus posticus had symptoms of tension type headache and migraine in the age group of 16-45 years.…”
Section: Resultsmentioning
confidence: 91%
“…[49][50][51] The PP is generally regarded as a simple anatomical variant. However, the compression of the nervous and vascular structures passing through the foramen (vertebral artery, periarterial plexus, and suboccipital nerve) may result in a combination of symptoms such as cervical migraine 49 ; neurosensory-type hearing loss 52 ; neck pain; vertigo; shoulder-arm pain; and, in some instances, even loss of postural muscle tone, consciousness, and vertebrobasilar insufficiency syndrome. 17 Severe headache is present in 56% to 90% of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Kimmerle's anomaly can be a cause for manifestation of chronic tension type headaches and neurosensory type hearing loss [13] and also for acute cerebrovascular disorders in vertebro basilar field [14] and can be an extravasal factor in respect of the vertebral artery causing a compression-stenosing -irritative effect. [15] Cushing KE et al have reported that presence of an arcuate foramen can cause tethering of the vertebral artery in the foramen and dissection can occur from repetitive trauma with movement of the neck [16].…”
Section: Discussionmentioning
confidence: 99%